2018
DOI: 10.1038/s41598-018-19880-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Slowly Rocking Bed on Sleep

Abstract: Rocking movements appear to affect human sleep. Recent research suggested a facilitated transition from wake to sleep and a boosting of slow oscillations and sleep spindles due to lateral rocking movements during an afternoon nap. This study aimed at investigating the effect of vestibular stimulation on sleep onset, nocturnal sleep and its potential to increase sleep spindles and slow waves, which could influence memory performance. Polysomnography was recorded in 18 males (age: 20–28 years) during three night… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 51 publications
2
49
3
Order By: Relevance
“…Because both somatosensory and vestibular systems send direct inputs to the thalamus [1,45,46], their rocking-induced rhythmic stimulation might entrain SOs and spindles within Table S2. thalamocortical circuits. Hence, this mechanism would in turn favor spindles' function in protecting sleep and explain why we also observed changes in the architecture of sleep (increase in N3 duration, decrease in arousals), unlike other studies in which pulsed sensory stimulations were used [8,12,13] or rocking was used only during the first 2 h of sleep [16]. Importantly, we demonstrated that the rocking-induced spindles had unaltered phase coupling with the SO.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…Because both somatosensory and vestibular systems send direct inputs to the thalamus [1,45,46], their rocking-induced rhythmic stimulation might entrain SOs and spindles within Table S2. thalamocortical circuits. Hence, this mechanism would in turn favor spindles' function in protecting sleep and explain why we also observed changes in the architecture of sleep (increase in N3 duration, decrease in arousals), unlike other studies in which pulsed sensory stimulations were used [8,12,13] or rocking was used only during the first 2 h of sleep [16]. Importantly, we demonstrated that the rocking-induced spindles had unaltered phase coupling with the SO.…”
Section: Discussioncontrasting
confidence: 47%
“…A shortening of sleep latency caused by sensory stimulations was previously reported in the pioneering study by Pompeiano and Swett (1962), who applied regular low-intensity cutaneous electric stimulations in cats [22], and by more recent studies in humans using electrical, olfactory, or rocking stimulations [7,16,[23][24][25]. Here, beyond a mere facilitation of sleep initiation with an overall reduction in sleep latency to N2 and a tendency to enter faster into N3, we also found that rocking profoundly modified the architecture of sleep, with an increase in N3 duration and a decrease in N2 (and N1) duration, while REM sleep remained unaffected.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations